Educação não formal democrática no YouTube: três estudos de caso - Kruse, Thaís Cristina (2023)
This research presents, in the form of case studies, non-formal education initiatives that occur on YouTube through the analysis of the channels Aza Njeri, Manual do Mundo and Sesc São Paulo (Bertioga), pointing their most recurrent and relevant characteristics, especially their potential of democratizing useful knowledge at low cost and shared access. Since the platform is an accessible space for the production (by the creators) and consumption (by the users) of knowledge, this study intends to identify the rich and creative cognitive opportunities in the access and the challenges of its uses, reflecting its limits, its veracity and mechanisms for capturing users' private data. This analysis takes into account that freedom of experimentation and creation can also promote negative social impacts, such as the spread of misinformation and content that does not carry democratic values. Authors such as Paulo Freire (2003, 2007), Michael Apple (2006) and Maria da Glória Gohn (2011) support our reflections on curriculum and education with Shoshana Zuboff (2019), Néstor García Canclini (2021) and Guia da Educação Midiática (2020), which address phenomena related to digital technologies. Among the results, the following variables were observed: the accessibility of content available on an open and freely accessible network becomes an opportunity to meet new, quick and diverse sources of information and to promote knowledge. It is also verified that such contents and activities in open networks complement or differ from those hegemonically established in the usual methodologies of formal school education